Affordable Housing and Individual Labor Market Outcomes - Wolfgang Dauth; Andreas Mense; Matthias Wrede (Institute of Labor Economics (IZA), 2024)
We investigate the employment effects of living in affordable housing. We develop a unique administrative data set of labor market biographies linked to affordable housing projects in five German cities. This allows us to follow individuals in affordable housing over almost 20 years. The funding scheme is similar to the American LIHTC program, so the results are applicable beyond Germany. We use an event study design to exploit the quasi-random timing and allocation of applicants to units. Our findings show that access to affordable housing increases labor income and job quality while decreasing the likelihood of being unemployed. We explain these results by four mechanisms. These mechanisms work through a higher centrality of affordable units, enabling investment in work-related skills, improved housing stability, and increasing work incentives due to reduced housing benefit payments.
Keywords: I31; I38; J13; R23; R38; 330; affordable housing; unemployment; urban labor market access; labor supply; housing policy